Gendering the Struggle: Women’s Voices of Resistance and the Jewish Movement in the Soviet Union - Nadia Iermakov; Nehemia Stern (Religions, 2024)
This article analyzes the contribution of women to the Soviet Union’s Jewish movement. We argue that an assessment of the personal stories of Jewish female activists in the former Soviet Union reveals a uniquely meaningful impact on the exodus of Jewry from the Soviet Union, the image of the Soviet Jewish struggle in the international arena, and the establishment of a human rights movements in its support. We explore who these women were, their personal identities, and through what factors they became so successful as prominent leaders in their communities as well as within international organizations. More broadly, by highlighting the link between women’s human rights activities and personal life stories, this article emphasizes a more nuanced analysis concerning the complexity of heroism within national freedom movements through its impact on their careers, mental health, and future destinies.